2018
DOI: 10.13170/aijst.7.1.8770
|View full text |Cite
|
Sign up to set email alerts
|

Compositions Optimization of Antang Corundum for Developing Advanced Ceramic

Abstract: -The research aims to study and optimize the formulation of materials required for advanced ceramic production using response surface methodology (RSM). In this research effort, the five (5) process independent variables studied with their corresponding levels are: Antang corundum powder, A (92.2 -100 %W); polyvinyl alcohol, B (0 -5 %W); CaO, C (0 -2.3 %W); MgO, D (0 -0.5 %W);and the sintering temperature, E (1200 -1500 °C).The mechanical property responses determined were density, ρ, compressive strength, C/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Normally, the ability of armour to stop bullets, ballistics effectiveness, is not determined by visual inspection but must be inferred from the results of live-firing test [40]. Sintered alumina ceramic (10 ×120 ×120 mm) prepared by sintering process [26] was used as the facial plate; and Table 4 gives the physical properties of the sintered alumina (AC-86.6). The ceramic was laminated onto 7×120×120 mm armour steel (donated by Defence Industries Corporation of Nigeria), Fig.…”
Section: Experimental Ballistic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, the ability of armour to stop bullets, ballistics effectiveness, is not determined by visual inspection but must be inferred from the results of live-firing test [40]. Sintered alumina ceramic (10 ×120 ×120 mm) prepared by sintering process [26] was used as the facial plate; and Table 4 gives the physical properties of the sintered alumina (AC-86.6). The ceramic was laminated onto 7×120×120 mm armour steel (donated by Defence Industries Corporation of Nigeria), Fig.…”
Section: Experimental Ballistic Studymentioning
confidence: 99%
“…It was reported that the reduction in layer thickness leads to increase in the system strength. Alumina ceramic had been previously prepared by sintering process from purified corundum [25,26]. This study strives to determine the ballistic influence of the ceramic on ceramic/steel composite as well as finding the optimum thickness of the ceramic required to make an applied component of ceramic/steel armour system for structural ballistic applications.…”
Section: Introductionmentioning
confidence: 99%